Hemiarthroplasty or total elbow arthroplasty for unreconstructable distal humeral fractures in patients aged over 65 years: a systematic review and meta-analysis of patient outcomes and complications. (1st May 2022) - Burden, Eleanor Grace; Batten, Timothy; Smith, Christopher; Evans, Jonathan P.
Abstract : Aims: Arthroplasty is being increasingly used for the management of distal humeral fractures (DHFs) in elderly patients. Arthroplasty options include total elbow arthroplasty (TEA) and hemiarthroplasty (HA); both have unique complications and there is not yet a consensus on which implant is superior. This systematic review asked: in patients aged over 65 years with unreconstructable DHFs, what differences are there in outcomes, as measured by patient-reported outcome measures (PROMs), range of motion (ROM), and complications, between distal humeral HA and TEA? Methods: A systematic review of the literature was performed via a search of MEDLINE and Embase. Two reviewers extracted data on PROMs, ROM, and complications. PROMs and ROM results were reported descriptively and a meta-analysis of complications was conducted. Quality of methodology was assessed using Wylde's non-summative four-point system. The study was registered with PROSPERO (CRD42021228329). Results: A total of 29 studies met the inclusion and exclusion criteria. The mean Disabilities of the Arm, Shoulder and Hand questionnaire (DASH) score was 19.6 (SD 7.5) for HA and 38 (SD 11.9) for TEA and the mean abbreviated version of DASH was 17.2 (SD 13.2) for HA and 24.9 (SD 4.8) for TEA. The Mayo Elbow Performance Score was the most commonly reported PROM across included studies, with a mean of 87 (SD 5.3) in HA and 88.3 (SD 5) in TEA. High complication rates were seen in both HA (22% (95% confidence interval (CI) 5 to 44)) and TEA (21% (95% CI 13 to 30), but no statistically significant difference identified. Conclusion: This systematic review has indicated PROMs and ROM mostly favouring HA, but with a similarly high complication rate in the two procedures. However, due to the small sample size and heterogeneity between studies, strength of evidence for these findings is low. We propose further research in the form of a national randomized controlled trial. Cite this article: Bone Joint J 2022;104-B(5):559–566.